Electrospinning with dual collection rings - Dalton, Paul D.; Klee, Doris; Möller, Martin (Polymer (Guilford), 2005)
The formation of electrospun poly(ɛ-caprolactone) (PCL) fibres between two collection rings is described, and the conversion of these fibres into a multi-filament yarn of is demonstrated. During electrospinning, when two grounded rings are placed equidistantly from the spinneret, an array of fibres is formed between the collection rings. These rapidly produced fibres are three-dimensionally suspended in air, and demonstrate low incidence of fibre splitting when lower voltages are applied. Such electrospun fibres, with a diameter of 1.26±0.19μm and a length between 40 and 100mm, were oriented and continuous. Furthermore, manufacture of the fibre array was easily achievable, reproducible and not subject to relatively small changes in spinneret-ground distance or applied voltage. Rotation of one of the collection rings results in a wound multi-filament yarn with a diameter below 5μm, and a length of 50mm.